Contents of Training High-Graded Specialists in Informational Computer Technologies within the Context of Cognitive Processes (Using Programming as an Example) - Golovin М.Б. (Journal of Information Technologies in Education (ITE), 2008)
The original graphic method of the activity object’s cognitive structure formalization and the logic of its formation is represented.